FSH HORMONE LEVELS IN BALI CATTLE WITH REPEATED MATING IN SOBANGAN VILLAGE, MENGWI SUBDISTRICT, BADUNG REGENCY, BALI - Ni Putu Amanda Sagita Putri; Desak Nyoman Dewi Indira Laksmi; I Made Damriyasa (Buletin Veteriner Udayana, 2024)
Repeat breeder is a condition where a female cow fails to become pregnant after artificial insemination (IB) or natural mating. This study aims to determine the number of results of FSH levels in Balinese cows that experience repeated breeding. The research was conducted by surveying the location directly to interview several farmers with questionnaires whose cattle experienced repeated mating problems, interviews using questionnaires and data analyzed descriptively. The research location was in Sobangan Village, Mengwi District. The samples used were 3-10 years old Balinese cows with HCS between 3-4. The results showed FSH levels in repeatedly mated cows 40.21 - 63.85 mIU/ml and normal cows 34.48 mIU/ml and 56.04 mIU/ml. It can be concluded that FSH levels are not associated with the occurrence of repeated mating. The results of this study can be used as a basis for further research by testing Luteinizing Hormone (LH) levels.